YangXue QingNao Wan, a Compound Chinese Medicine, Attenuates Cerebrovascular Hyperpermeability and Neuron Injury in Spontaneously Hypertensive Rat: Effect and Mechanism - Jiao, Ying-Qian; Huang, Ping; Yan, Li; Sun, Kai; Pan, Chun-Shui; Li, Quan; Fan, Jing-Yu; Ma, Zhi-Zhong; Han, Jing-Yan (Frontiers in Physiology, 2019)
Objective The purpose of the study was to explore the effect of YangXue QingNao Wan (YXQNW), a compound Chinese medicine, on cerebrovascular hyperpermeability, neuronal injury, and related mechanisms in spontaneously hypertensive rat (SHR). Methods Fourteen-week-old male SHR were used, with Wistar Kyoto (WKY) rats as control. YXQNW (0.5 g/kg/day), enalapril (EN, 8 mg/kg/day), and nifedipine (NF, 7.1 mg/kg/day) were administrated orally for 4 weeks. To assess the effects of the YXQNW on blood pressure, the systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean blood pressure (MBP) were measured. After administering the drugs for 4 weeks, the cerebral blood flow (CBF), albumin leakage from microvessels in middle cerebral artery (MCA)-dominated area, and the number and morphology of microvessels were assessed in the hippocampus area and cortex. Neuronal damage and apoptosis were assessed by Nissl staining and TUNEL staining. To assess the mechanisms of cerebrovascular hyperpermeability, we performed immunofluorescence and Western blot to assess the expression and integrity of cerebral microvascular tight junction (TJ) and caveolin-1 (Cav-1) in cortex. Energy metabolism and Src-MLC-MLCK pathway in cortex were assessed then for elucidating the underlying mechanism of the observed effect of YXQNW. Results Spontaneously hypertensive rat exhibited higher blood pressure, Evans blue (EB) extravasation, albumin leakage, increased brain water content, decreased CBF, perivascular edema, and neuronal apoptosis in the hippocampus and cortex, all of which were attenuated by YXQNW treatment. YXQNW inhibited the downregulation of TJ proteins, mitochondrial Complex I, Complex II, and Complex V, and upregulation of caveolin-1, inhibiting Src/MLCK/MLC signaling in SHR. YXQNW combined with EN + NF revealed a better effect for some outcomes compared with either YXQNW or EN + NF alone. Conclusion The overall result shows the potential of YXQNW to attenuate blood–brain barrier (BBB) breakdown in SHR, which involves regulation of energy metabolism and Src/MLCK/MLC signaling. This result provides evidence supporting the application of YXQNW as an adjuvant management for hypertensive patients to prevent hypertensive encephalopathy.